Are We Ready for the Use of Foxp3+ Regulatory T Cells for Immunodiagnosis and Immunotherapy in Kidney Transplantation? - Francisco Salcido-Ochoa; Nurhashikin Yusof; Susan Swee-Shan Hue; Doreen Haase; Terence Kee; Olaf Rotzschke (Journal of Transplantation)
The existence of T-cell subsets naturally committed to perform immunoregulation has led to enthusiastic efforts to investigate their role in the immunopathogenesis of transplantation. Being able to modulate alloresponses, regulatory T cells could be used as an immunodiagnostic tool in clinical kidney transplantation. Thus, the measurement of Foxp3 transcripts, the presence of regulatory T cells in kidney biopsies, and the phenotypic characterisation of the T-cell infiltrate could aid in the diagnosis of rejection and the immune monitoring and prediction of outcomes in kidney transplantation. Interestingly, the adoptive transfer of regulatory T cells in animal models has been proven to downmodulate powerful alloresponses, igniting translational research on their potential use as an immunomodulatory therapy. For busy transplant clinicians, the vast amount of information in the literature on regulatory T cells can be overwhelming. This paper aims to highlight the most applicable research findings on the use of regulatory T cells in the immune diagnosis and potential immunomodulatory therapy of kidney transplant patients. However, can we yet rely on differential regulatory T-cell profiles for the identification of rejection or to tailor patient's immunosuppression? Are we ready to administer regulatory T cells as inductive or adjunctive therapy for kidney transplantation?